2021
DOI: 10.1200/op.21.00276
|View full text |Cite
|
Sign up to set email alerts
|

Moral Distress Among Oncology Social Workers

Abstract: PURPOSE: Literature on moral distress among oncology social workers (OSWs) is sparse. The aim of the current study was to examine the prevalence of moral distress and its domains of influence, and to identify demographic and work-related characteristics associated with moral distress among OSWs. METHODS: Data came from the Oncology Social Work Competencies, Opportunities, Roles, and Expertise survey, conducted from August to September 2020 (during the COVID-19 global pandemic). Data collected included demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…[3][4][5][6][7][8] Despite the advances in our understanding of burnout among members of the oncology team, there remains a limited understanding of the impact of moral distress (MD) and its relationship to burnout. [9][10][11][12] MD is the result of barriers or constraints that prevent providers from carrying out what they believe to be ethically appropriate care. Barriers to carrying out what health care providers believe to be the right care can be related to patient-, team-, and institution-level constraints.…”
Section: Corresponding Author Original Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8] Despite the advances in our understanding of burnout among members of the oncology team, there remains a limited understanding of the impact of moral distress (MD) and its relationship to burnout. [9][10][11][12] MD is the result of barriers or constraints that prevent providers from carrying out what they believe to be ethically appropriate care. Barriers to carrying out what health care providers believe to be the right care can be related to patient-, team-, and institution-level constraints.…”
Section: Corresponding Author Original Contributionsmentioning
confidence: 99%
“…3-8 Despite the advances in our understanding of burnout among members of the oncology team, there remains a limited understanding of the impact of moral distress (MD) and its relationship to burnout. 9-12…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating the relationship between MD and years of practice reported mixed results. Some studies recorded a higher level of MD in healthcare providers with more years of practice [ 6 , 19 , 20 ], as repeated exposure to MD experiences would increase the perception of distress. Other studies found that nurses lacking experience in dealing with ethically challenging situations at the beginning of their professional careers may be at greater risk of MD [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Research investments must be aimed towards generating sustainable means of care delivery in order to bolster long-term clinician wellbeing and mitigate distress peri- and post-pandemic, particularly in light of substantive evidence describing the burnout and moral suffering of healthcare workers - including palliative care and oncology clinicians - that long preceded COVID-19 and has been exacerbated by myriad sequelae of this public health emergency. 36-40…”
Section: Discussionmentioning
confidence: 99%